TANTANGAN DAN STRATEGI IMPLEMENTASI GREEN HUMAN RESOURCE MANAGEMENT DI ERA DIGITAL - Pauwah, Irma (Indragiri Research Center (ingreat), 2025)
This research investigates how Green Human Resource Management (GHRM) and the principles of Diversity, Equity, and Inclusion (DEI) are integrated in developing sustainable, inclusive, and innovative organizations, as well as in preparing future leaders. The research delves into the significant role of Green Organizational Culture as a mediator that connects GHRM practices, environmentally-based training, and green innovation, ultimately leading to improved employee engagement and operational efficiency. The results also suggest that successful implementation of GHRM can lessen carbon footprints, improve natural resource management, and foster diversity in the workplace. Simultaneously, the DEI principles have been shown to reinforce talent retention, collaboration, and employee satisfaction, eventually boosting organizational performance. Nevertheless, this research also highlights obstacles in implementing GHRM and DEI, such as resistance to change and work-related stress, which call for adaptive and collaborative strategies. Therefore, the integration of GHRM and DEI is anticipated to establish an innovative and sustainable workplace and to prepare future leaders who are adaptive to change and global challenges.